1998
DOI: 10.1002/(sici)1096-9837(199801)23:1<69::aid-esp823>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Influence of vegetation cover on sand transport by wind: field studies at Owens Lake, California

Abstract: Field studies conducted at Owens Lake, California, provide direct measurements of sand flux on sand sheets with zero to 20 per cent cover of salt grass. Results from 12 different sand transport events show that aerodynamic roughness length and threshold wind shear velocity increase with vegetation cover as measured by vertically projected cover and roughness density (λ). This results in a negative exponential decrease in sediment flux with increasing vegetation cover such that sand transport is effectively eli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
238
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 353 publications
(265 citation statements)
references
References 22 publications
17
238
2
Order By: Relevance
“…Detailed evaluations of roughness parameters associated with vegetation are difficult because of the complex shapes and heterogeneous clustering of plants (Lancaster and Baas, 1998;Arens et al, 2001), but qualitative evaluations of the role of vegetation can be made using visual estimates of key variables. Height of vegetation (an estimate of roughness) and percentage ground cover (an estimate of potential for entrainment of surface sediments) were measured in a 1 × 1 m grid between 12 and 20 March 2003.…”
Section: Methodsmentioning
confidence: 99%
“…Detailed evaluations of roughness parameters associated with vegetation are difficult because of the complex shapes and heterogeneous clustering of plants (Lancaster and Baas, 1998;Arens et al, 2001), but qualitative evaluations of the role of vegetation can be made using visual estimates of key variables. Height of vegetation (an estimate of roughness) and percentage ground cover (an estimate of potential for entrainment of surface sediments) were measured in a 1 × 1 m grid between 12 and 20 March 2003.…”
Section: Methodsmentioning
confidence: 99%
“…Field studies have demonstrated that the presence of vegetation effectively reduces aeolian sand transport, and vice versa (Ash and Wasson, 1983;Buckley, 1987;Wolfe and Nickling, 1993;Brown, 1997;Lancaster and Baas, 1998;Levin et al, 2008;Okin, 2008). The complex interplay and feedbacks between vegetation growth and sand transport drives the dune system towards one of the two end-member states: active or stabilized.…”
Section: Characterizing Dune Activitymentioning
confidence: 99%
“…In their exhaustive analysis on Quaternary stratigraphy and environments of the Arabian Peninsula, Glennie and Singhvi [51] confirm the long-term persistence of the Shamal, but state a generally weaker intensity during interglacials. While decreasing trends of the NAO and the ISM may indicate a Shamal stronger than today over most of the Holocene, and hence, higher migration rates, wetter conditions during the early to mid-Holocene transition identified in many parts of the Arabian Peninsula [50,[52][53][54] may have stimulated vegetation cover slowing down sand flux and migration speed [4,11,55,56]. The ways in which these competing mechanisms have led to deviations from the migration rates identified in the shorter term multitemporal satellite and aerial image analysis of this study over millennial time scales remain a matter of speculation.…”
Section: Long-term Perspective On Shamal Controlsmentioning
confidence: 99%